Maria Nguyen: capstone - Nguyen, Maria, artist (Colorado State University. Libraries, 2021)
The artist's statement: It is a firm belief of mine that graphic design is not designing for yourself, but rather designing for others. It would be most accurate to describe my work as a union of my personal style and the intended impact it should have on its audience. My work is meant to ask questions and provoke thoughts, as well as play into the surreal and subconscious. I am interested in creating thoughts in the minds of my viewers, whether they be positive or negative. My work also heavily considers the needs of the users and viewers. I believe that combining user research, wants, and needs with some much-needed visual impact is very important when creating design projects in graphic design. I primarily work using digital illustration, digital design, wireframing, and prototyping. It is important to me to create iterations and build on them until it becomes a fully functioning, fully fleshed out product that is successful, both in terms of function and aesthetics.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: graphic design